2022
DOI: 10.1038/s41416-022-01871-x
|View full text |Cite
|
Sign up to set email alerts
|

Talking about Risk, UncertaintieS of Testing IN Genetics (TRUSTING): development and evaluation of an educational programme for healthcare professionals about BRCA1 & BRCA2 testing

Abstract: Background Mainstreaming of germline testing demands that all healthcare professionals have good communication skills, but few have genetic testing and counselling experience. We developed and evaluated educational workshops—Talking about Risk & UncertaintieS of Testing IN Genetics (TRUSTING). Contents included: presentations and exercises, an interview with a geneticist about BRCA testing, screening and prevention implications, filmed interactions between surgeons, a genetic counsellor and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It would impose too heavy of a burden on genetic counsellors to offer pre-test counselling too all these patients. Currently, mainstreaming of genetic care, in which pretest counselling by nongenetic health care professionals is integrated into routine care, is studied by multiple groups and seems feasible and resource efficient [50][51][52][53][54][55][56][57][58] . Mainstreaming has many advantages, all patients (that consented) can be included and genetic counsellors only get patients referred with a proven PGV.…”
Section: Discussionmentioning
confidence: 99%
“…It would impose too heavy of a burden on genetic counsellors to offer pre-test counselling too all these patients. Currently, mainstreaming of genetic care, in which pretest counselling by nongenetic health care professionals is integrated into routine care, is studied by multiple groups and seems feasible and resource efficient [50][51][52][53][54][55][56][57][58] . Mainstreaming has many advantages, all patients (that consented) can be included and genetic counsellors only get patients referred with a proven PGV.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sampling experiences from similar studies [17,29], our study aimed to recruit at least n = 100 participants. To evaluate the training, we assessed participants' selfefficacy expectations regarding patient-centered communication in the context of genetic The second part of the training module revolves around issues that are particularly relevant for women after genetic testing.…”
Section: Methods Of Evaluation Of the Trainingmentioning
confidence: 99%
“…For example, Fallowfield et al (2022) developed a training program for health care professionals who are involved in communicating BRCA1/2 genetic test results in the UK. They demonstrated that knowledge, communication skills and confidence improved significantly after the intervention [17]. Notably, genetic counselling practices and referral systems differ widely between countries [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This training is seen by its organisers as an essential prerequisite to facilitating mainstreaming, and has been shown to be successful in improving knowledge, communication skills and self-confidence in a cohort of delegates, 21 of whom were surgeons. 19 Similar, smaller-scale training courses also exist in many centres where mainstreaming is already being introduced such as in Nottingham. 20…”
Section: Preparing For Mainstreamingmentioning
confidence: 99%